The incidences of oxidative-stress occurrence following two metabolic support measures in critically ill patients - Asie Moosivand; Ramin Abrishami; Mohammad Abdollahi; Arezoo Ahmadi; Mojtaba Mojtahedzadeh (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: A high percentage of patients admitted to the Intensive Care Unit (ICU) have Systemic Inflammatory Response Syndrome (SIRS) criteria. Free radicals play an important role in initiation and development of SIRS. The purpose of this study was to assess and compare the molecular changes of cellular antioxidant power in patients with SIRS who received enteral nutrition (EN) or EN combined with parenteral nutrition (PN). Methods: Two groups of 10 patients were enrolled in this randomized, controlled clinical trial. Those in the treatment group received EN+PN and the control group received only EN. Venous blood samples were taken just prior to initiation of nutritional support and then 24, 48 and 72 hours following entry into the study for examination of antioxidant parameters including total thiol, total antioxidant capacity and lipid peroxidation. Results: The two supportive regimens had different affects on total antioxidant capacity (P=0.005). In the EN group the amount of total antioxidant capacity was not significantly different in different days (P>0.05), but in the EN+PN group it was significantly different on third and forth days as compared to the first day. The two other parameters had no significant differences between the two groups. Conclusion: These  results  are  suggesting  that  an  increase  in  oxidative  stress  bio- markers are not necessarily related to the route of pharmaconutrition and may occurindependently during metabolic support measures.